2023
DOI: 10.1049/htl2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance factors of telemedicine technology during Covid‐19 pandemic among health professionals: A qualitative study

Abstract: Health professionals are the main users of telemedicine systems, and their acceptance will contribute to the successful implementation of this technology. The objective of this study is to provide a better understanding of the issues surrounding the acceptance of telemedicine technology by Moroccan health professionals in the public sector, in the preparation for a possible generalization of this technology in Morocco. Method: Following a literature review, the authors mobilized a modified version of the unifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…As for the identified studies that were conducted after the pandemic was declared, patients’ and HCPs’ acceptability toward or satisfaction with remote care was high in every case [ 50 - 56 ]. This is in line with previous studies that found a positive attitude toward telemedicine use among patients and HCPs during the pandemic [ 77 , 78 ]. However, such attitudes might have been influenced by the need to adopt remote care technologies imposed by the pandemic [ 65 ], rather than these being an optional alternative.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As for the identified studies that were conducted after the pandemic was declared, patients’ and HCPs’ acceptability toward or satisfaction with remote care was high in every case [ 50 - 56 ]. This is in line with previous studies that found a positive attitude toward telemedicine use among patients and HCPs during the pandemic [ 77 , 78 ]. However, such attitudes might have been influenced by the need to adopt remote care technologies imposed by the pandemic [ 65 ], rather than these being an optional alternative.…”
Section: Discussionsupporting
confidence: 93%
“…From patients’ perspectives, the reported benefits of telemedicine consultations are related to their convenience, time and cost efficiency, ease of access to HCPs’ insights, and informational aspects [ 39 , 45 , 47 , 48 , 52 , 55 , 56 ]. Barriers to these aspects have been identified as limitations to health care access for patients with chronic conditions [ 78 - 81 ]. The findings of this scoping review indicate that internet-based modalities can potentially address some of those pertinent barriers, especially considering that some patients viewed internet-based visits as comparable to in-person visits [ 40 , 42 , 50 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acceptance of telemedicine technology among health professionals was studied by Mohammed et al (2023) in the context of the Moroccan public sector [10]. Their research contributes to understanding the factors influencing the successful implementation of telemedicine technology.…”
Section: Related Workmentioning
confidence: 99%
“…In this equation (10), m represents the number of iterations, ρ represents the learning rate, and h m (x) represents the newly added weak model.…”
Section: Fig 6 Gradient Boosting Algorithmmentioning
confidence: 99%
“…Actually, it is a well-established fact in health-related information technology (IT) literature that certain factors can influence physicians' perception of the use of technology such as telemedicine [77][78][79], electronic medical records (EMR) [80][81][82][83], clinical decision support systems [84][85][86], and mobile health (m-health) applications [87][88][89][90][91]. Behavioral and technology acceptance models are often used to explain user behavior [92][93][94][95].…”
Section: Econsult Services Worldwidementioning
confidence: 99%